High-risk additional chromosomal abnormalities at low blast counts herald death by CML - Hehlmann, Ruediger; Voskanyan, Astghik; Lauseker, Michael; Pfirrmann, Markus; Kalmanti, Lida; Rinaldetti, Sebastien; Kohlbrenner, Katharina; Haferlach, Claudia; Schlegelberger, Brigitte; Fabarius, Alice; Seifarth, Wolfgang; Spiess, Birgit; et al. (Leukemia, 2020)
Blast crisis is one of the remaining challenges in chronic myeloid leukemia (CML). Whether additional chromosomal abnormalities (ACAs) enable an earlier recognition of imminent blastic proliferation and a timelier change of treatment is unknown. One thousand five hundred and ten imatinib-treated patients with Philadelphia-chromosome-positive (Ph+) CML randomized in CML-study IV were analyzed for ACA/Ph+ and blast increase. By impact on survival, ACAs were grouped into high risk (+8, +Ph, i(17q), +17, +19, +21, 3q26.2, 11q23, -7/7q abnormalities; complex) and low risk (all other). The presence of high- and low-risk ACAs was linked to six cohorts with different blast levels (1%, 5%, 10%, 15%, 20%, and 30%) in a Cox model. One hundred and twenty-three patients displayed ACA/Ph+ (8.1%), 91 were high risk. At low blast levels (1-15%), high-risk ACA showed an increased hazard to die compared to no ACA (ratios: 3.65 in blood; 6.12 in marrow) in contrast to low-risk ACA. No effect was observed at blast levels of 20-30%. Sixty-three patients with high-risk ACA (69%) died (n = 37) or were alive after progression or progression-related transplantation (n = 26). High-risk ACA at low blast counts identify end-phase CML earlier than current diagnostic systems. Mortality was lower with earlier treatment. Cytogenetic monitoring is indicated when signs of progression surface or response to therapy is unsatisfactory.
EVALuna2:216177